2014
DOI: 10.1155/2014/481482
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of TRα1 in Cardiac Repair: Potential Therapeutic Implications

Abstract: Thyroid hormone (TH) is critical for adapting living organisms to environmental stress. Plasma circulating tri-iodothyronine (T3) levels drop in most disease states and are associated with increased oxidative stress. In this context, T3 levels in plasma appear to be an independent determinant for the recovery of cardiac function after myocardial infarction in patients. Thyroid hormone receptor α1 (TRα1) seems to be crucial in this response; TRα1 accumulates to cell nucleus upon activation of stress induced gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…Moreover, it is possible that the augmentation in the anti‐TRα positive myonuclei of the Bsm could be related to the polymyositis observed in this muscle. The fact that the TRα is involved in inflammatory and regeneration processes in cardiac striated fibers and the liver, supports this proposal …”
Section: Discussionsupporting
confidence: 59%
“…Moreover, it is possible that the augmentation in the anti‐TRα positive myonuclei of the Bsm could be related to the polymyositis observed in this muscle. The fact that the TRα is involved in inflammatory and regeneration processes in cardiac striated fibers and the liver, supports this proposal …”
Section: Discussionsupporting
confidence: 59%
“…Some factors may predict a more pronounced decline in T3 levels, such as worsening angina pectoris preceding acute myocardial infarction, known chronic heart failure or previous myocardial infarction and diabetes mellitus (89). Low T3 levels also induce oxidative stress and increase apoptotic rate, which may worsen ventricular dysfunction (90). Therefore, THs levels are an important factor modulating left ventricular structure, function and geometry during the late post-myocardial infarction period (91).…”
Section: The Impact Of Thyroid Hormone Dysfunction On Myocardial Ischmentioning
confidence: 99%
“…TH signaling is complex and becoming more so as new information arises. Since there are many compre-hensive reviews on the topic (8,32,82,91,97), it will be discussed only briefly here. THs signal genomically through nuclear TRs.…”
Section: What Have We Learned From Animal Studies?mentioning
confidence: 99%
“…Animal and human studies have generally shown downrgulation of TRs in hypertrophy and HF, suggesting another mechanism by which TH function may be reduced even when serum hormone levels are normal (62,63,100). Nonetheless, there is considerable controversy in this area of research, particularly with regard to results from gene-targeted mouse studies that may represent more extreme changes than those typically occuring in real life (97). Impaired TR␣ signaling, in particular, likely plays a major role in cardiac dysfunction and adverse remodeling in heart diseases (88,98).…”
Section: What Have We Learned From Animal Studies?mentioning
confidence: 99%
See 1 more Smart Citation